Potential application of pure silica optical flat fibers for radiation therapy dosimetry - Alawiah, A.; Bauk, S.; Abdul-Rashid, H.A.; Gieszczyk, W.; Hashim, S.; Mandiraji, G.A.; Tamchek, N.; Bradley, D.A. (Elsevier, 2015)
Pure silica optical flat fibers (FF) have been proposed as the basis for a novel radiation sensor by the measurement of the thermoluminescence (TL) produced. In this paper the 17, performance of the FFs were studied. Using a linear accelerator (LINAC) delivering doses in the range 0.2-10.0 Gy, the TL dosimetric glow curves of the FFs were studied with respect to 6 MeV electron and 6 MV photon beams. When exposed to 6 MeV electron irradiation, the pure silica FFs displayed a supralinear response starting from 2 Gy up to 10.0 Gy. While for 6 MV photon irradiation, the FFs shows linear characteristic (f(D) = 1) nearly up to 2 Gy. The TL intensity (I-m) of the main peak of FFs is 1.5 times higher for 6 MeV electron beams than for 6 MV photon beams. The maximum peak temperature (T-m) it is not affected by the type of irradiation used at the same dose while the maximum TL intensity (I-m) was found to be dependent on the type of radiation used. Overall results indicate that the pure silica FFs can be used as radiation sensors in the high-dose therapy dosimetry. (C) 2014 Elsevier Ltd. All rights reserved.